A calibrated chronology of biochemistry reveals a stem line of descent responsible for planetary biodiversity - Caetano-Anollés, Gustavo; Mittenthal, Jay E.; Caetano-Anollés, Derek; Kim, Kyung Mo (Frontiers in Genetics, 2014)
Time-calibrated phylogenomic trees of protein domain structure produce powerful chronologies describing the evolution of biochemistry and life. These timetrees are built from a genomic census of millions of encoded proteins using models of nested accumulation of molecules in evolving proteomes. Here we show that a primordial stem line of descent, a propagating series of pluripotent cellular entities, populates the deeper branches of the timetrees. The stem line produced for the first time cellular grades ~2.9 billion years (Gy)-ago, which slowly turned into lineages of superkingdom Archaea. Prompted by the rise of planetary oxygen and aerobic metabolism, the stem line also produced bacterial and eukaryal lineages. Superkingdom-specific domain repertoires emerged ~2.1 Gy-ago delimiting fully diversified Bacteria. Repertoires specific to Eukarya and Archaea appeared 300 millions years later. Results reconcile reductive evolutionary processes leading to the early emergence of Archaea to superkingdom-specific innovations compatible with a tree of life rooted in Bacteria.